Eksistensi Ratam Bagi Penanaman Visi Dan Misi Prodi Teologi Hindu Di STAHN Mpu Kuturan Singaraja - I Wayan Kariarta; Komang Heriyanti; Ni Made Evi Kurnia Dewi (Jayapangus Press, 2021)
Ratam activities in the Hindu Theology Study Program are held in the framework of campus life orientation for new students (maba). In the implementation of ratam activities there are efforts to build communication and familiarity between all academic communities in the Hindu Theology Study Program. The vision of the Hindu Theology Study Program is: